De olhar e olhares: a ficção urbana de Alencar e as tramas sociais - Silva, Debora Reis da (2007)
The objective of this essay is to investigate the presence of sight in José de Alencar s urban fiction. Initially, it is proposed to understand the place where this cultural gesture has in society since modernity, read through Benjamin s and Baudelaire s attentive look, which gives the origin to what we call today sight society . This work also focus on a Brazilian desire for modernity, expressed on Alencar s novels, which shows the necessity to be mirrored in the other s vision and, at the same time, to display oneself to others , revelling a social life wrapped by a voyeuristic / exhibitionist behaviour. The writer appears as a world privileged viewer, who constantly looks for the quality of its look. The analyses of Encarnação, Diva and Senhora novels also gives the possibility to discuss the conflict, announced by the Brazilian writer, motivated by two different ways of those favours the world material vision , whilst the other defends, what we consider, the spiritual vision . One of the consequences of this imbalance is the dizziness state based on the necessity for a stable relationship between the being and the resemblance